당근 유기재배를 위한 검은잎마름병과 검은무늬병 종자소독제 선발 - 이재은(Jae Eun Lee); 용영록(Young Rok Yeoung); 권순배(Soon Bae Kwon); 김병섭(Byung Sup Kim) (Sigmulbyeong yeon'gu, 2011)
This study was conducted to control the seed borne pathogens (Alternaria spp.) of carrot and to examine the seed germination rate by using 13 environment friendly agricultural materials instead of conventional chemicals for organic cultivation. The growth inhibiting effects on pathogens showed the different responses according to each agricultural material and effective 7 materials against seed borne pathogens were selected. Among 7 materials, the carrot seeds sterilized with plant extracts, Tanger Stop and Land Saver were not germinated at all. The germination rate of seeds sterilized with other materials showed the similar levels with reference chemical (Benlate-T) and non-treated seeds. Infection rates of seeds sterilized with seaweed extract, Bellopper for controlling A. radicina and plant extract, Ssial-100 for A. dauci were similar or low infection rate compared with reference chemical. The germination rate and root length of seeds sterilized with Bellopper and Ssial-100 was similar or superior to those of chemical sterilized seeds. The optimal condition seemed to be a little bit different depending on the concentration of materials. As a result, the sterilization of carrot seeds by using the environment friendly materials could be effectively utilized as a technology to inhibit the infection of seed-borne pathogens. 본 연구는 당근의 유기재배를 위하여 13개의 친환경 제제를 이용한 당근의 Alternaria spp.에 의한 종자전염성 병원균 방제 및 종자 발아율 조사를 수행하였다. 병원균의 생장억제 효과는 친환경 제제 별로 차이를 보였으며 효과가 좋은 7개 제제를 선발하였다. 7개 친환경제제별종자소독 후 발아율 조사에서는 식물 추출물인 탄저스탑과 랜드세이버 제제로 소독된 종자는 발아가 전혀 되지 않았으며 다른 친환경제제에서 소독된 종자의 발아율은 대조약제(Benlate-T)와 무처리 종자의 발아율과 비슷하였다. 탄저스탑과 랜드세이버를 제외시킨 감염율 조사에서는 A. radicina 균에 대한 해조류 추출물인 벨로퍼, A. dauci 균은 식물 추출물인 씨알-100으로 소독된 종자가 감염율이 10% 미만으로 대조약제와 비슷하거나 낮게 나타났다. 이들 제제는 뿌리길이 및 유묘검정 발아율 조사도 대조약제로 소독한 종자와 비슷하거나 우수한 것으로 조사 되었다. 본 시험의 결과로 보아 종자소독의 최적의 조건은 약제별 농도에 따라 다소 다르며 친환경 제제를 이용한 종자소독은 종자전염성 병원균을 효과적으로 억제할 수 있는 기술로 활용될 수 있다.